Analisis Gap Kepentingan dan Kepuasan Pelanggan : Suatu Pendekatan Evaluasi Mutu Pelayanan - Fortunisa, Ananda (Business and Management Review, 2011)
The purpose of this paper is to provide same insight (1) service quality evaluation by proposing the importance-performance analysis as valuable tool to ensure multi-perspective evaluation and by customer satisfaction index, then (2) to know what priority attributes have to keep up the good work to achieve customer satisfaction. Data were obtained from 100 Esia customers who use service transactions online payment points wich sampling technique is convenience sampling. Data processed by using Importance Performance Analysis (IPA) methode and Customer Satisfaction Index (CSI). The IPA results showed by cartesius diagram and describes about the attribute fill in each quadran which have different meanings. Analysis of the level of concordance shows that lowest quality of service factors is the emphaty (78.60%), whereas the highest level is tangible dimension (89.45%). Based on the CSI calculations customer satisfaction is 72.17%. Keywords: Customer Expectation, Customer Satisfaction, Service Quality